2019
DOI: 10.1002/jgh3.12257
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of the lidocaine injection method during esophageal endoscopic submucosal dissection

Abstract: Background and Aim Esophageal endoscopic submucosal dissection (ESD) is often technically difficult due to intraoperative body movements. The level of sedation can be increased to suppress body movements, but this may not be successful in all cases. Using local analgesics for submucosal injection during ESD may aid in conscious sedation. This study evaluated the feasibility of the lidocaine injection method (LIM) during esophageal ESD. Methods Twenty‐nine patients with superficial esophageal cancer were enroll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
(92 reference statements)
0
1
0
Order By: Relevance
“…Recently, it was demonstrated that 2% lidocaine can effectively inhibit intestinal peristalsis in human experiments [30]. Lidocaine [31,32] is an amide-type local anaesthetic that relaxes smooth muscles. The safety and efficacy of lidocaine injections during endoscopic submucosal dissection have been previously reported [33]; however, the efficacy and safety of topical spraying lidocaine during polypectomy have not yet been investigated; particularly, they have not been investigated in the sigmoid colon, which has the highest peristalsis rate, poorest visual field, and lowest polyp resection rate.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was demonstrated that 2% lidocaine can effectively inhibit intestinal peristalsis in human experiments [30]. Lidocaine [31,32] is an amide-type local anaesthetic that relaxes smooth muscles. The safety and efficacy of lidocaine injections during endoscopic submucosal dissection have been previously reported [33]; however, the efficacy and safety of topical spraying lidocaine during polypectomy have not yet been investigated; particularly, they have not been investigated in the sigmoid colon, which has the highest peristalsis rate, poorest visual field, and lowest polyp resection rate.…”
Section: Discussionmentioning
confidence: 99%